Determinants of left atrium thrombi in scheduled cardioversion: an ENSURE-AF study analysis. Issue 11 (22nd August 2019) - Merino, Jose L; Lip, Gregory Y H; Heidbuchel, Hein; Cohen, Aron-Ariel; De Caterina, Raffaele; de Groot, Joris R; Ezekowitz, Michael D; Le Heuzey, Jean-Yves; Themistoclakis, Sakis; Jin, James; Melino, Michael; Winters, Shannon M; et al.
Abstract: Aims: ENSURE-AF (NCT 02072434) was the largest prospective randomized clinical trial of anticoagulation for cardioversion in atrial fibrillation (AF), which also provides the largest prospective dataset for transoesophageal echocardiography (TOE) prior to cardioversion. This ancillary analysis investigated determinants of TOE-detected left atrium thrombi (LAT) in patients scheduled for electrical cardioversion (ECV). Methods and results: The ENSURE-AF multicentre PROBE evaluation trial compared edoxaban 60 mg once daily (QD) with enoxaparin/warfarin in 2199 subjects undergoing ECV of non-valvular AF. Patients were stratified by the use of TOE, anticoagulant experience, and selected edoxaban dose. Electrical cardioversion was cancelled or deferred when TOEdetected LAT. In total, 1183 subjects were stratified to the TOE arm and LAT was reported in 91 (8.2%). In univariate analysis, age ≥75 years (26.4% vs. 16.9%, P = 0.0308), lower weight (86.5 ± 15.0 vs. 90.7 ± 18.0 kg, P = 0.0309), lower creatinine clearance (80.1 ± 30.6 vs. 93.2 ± 33.9 mL/min, P = 0.0007), heart failure (59.3% vs. 43.0%, P = 0.0029), and diuretic treatment (53.9% vs. 40.1%, P = 0.0141) were more prevalent in the LAT group. Non-significant trends were seen for higher mean CHA2 DS2 -VASc score (3.0 ± 1.41 vs. 2.7 ± 1.48, P = 0.0571) and more prevalent anticoagulation use prior to enrolment (60.4% vs. 50.3%, P = 0.0795) in the LAT group. In logistic regression analysis, age ( P = 0.0202) and heart failure ( P = 0.0064) were independently associated with LAT. Conclusion: Elective ECV is commonly cancelled or deferred due to TOE-detected LAT in patients with non-valvular AF. Age ≥75 years and heart failure were associated with the presence of LAT.